2023
DOI: 10.1186/s12944-023-01852-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of the time course of Chinese visceral adiposity index accumulation with cardiovascular events in patients with hypertension

Abstract: Background The Chinese visceral adiposity index (CVAI), a simple surrogate measure of visceral fat, is significantly associated with cardiovascular disease (CVD) risk in the general population. This study aimed to evaluate the association of cumulative CVAI (cumCVAI) exposure and its accumulation time course with CVD risk among patients with hypertension. Methods This prospective study involved 15,350 patients with hypertension from the Kailuan Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Interestingly, Wang et al [ 47 ] found in the southwestern Chinese population that CVAI serves as a robust predictive indicator for cardiovascular diseases in females, with significant predictive power observed only among female participants, while a gender difference was not evident in our study. Wu et al [ 48 ] concluded from their study on the hypertensive population that prolonged presence in high CVAI and greater duration of exposure to high CVAI could elevate the risk of cardiovascular diseases. Notably, early accumulation of CVAI posed a higher risk compared to later accumulation, which indirectly supported our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wang et al [ 47 ] found in the southwestern Chinese population that CVAI serves as a robust predictive indicator for cardiovascular diseases in females, with significant predictive power observed only among female participants, while a gender difference was not evident in our study. Wu et al [ 48 ] concluded from their study on the hypertensive population that prolonged presence in high CVAI and greater duration of exposure to high CVAI could elevate the risk of cardiovascular diseases. Notably, early accumulation of CVAI posed a higher risk compared to later accumulation, which indirectly supported our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…The China Health and Retirement Longitudinal Study, including 7242 middle-aged and elderly residents, showed that CVAI was associated with a 17% increased risk of incident stroke ( 44 ). Two cohort studies conducted in Xinjiang and Tangshan showed that CVAI was associated with an elevated risk of cardiovascular events in patients with hypertension and type 2 diabetes ( 45 , 47 ). In line with these findings, the present study identified a positive association between CVAI and the risk of CMM in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been increasing evidence that visceral adipose tissue is more closely associated with the onset of hypertension than subcutaneous fat or total fat. Gold standard techniques employed to assess visceral obesity include magnetic resonance imaging (MRI) and computed tomography (CT), however, these methods are not commonly utilized in clinical practice and epidemiological research owing to their inconvenience, high cost and radiation exposure to humans ( 5 ). Xia et al devised the Chinese visceral adiposity index (CVAI) by drawing upon the visceral obesity index (VAI).…”
Section: Introductionmentioning
confidence: 99%